Effect of Adding Nanoclay (Hallosite) On the Thermal Properties of Unsaturated Polyester Resin - Nadher Hlail Jaddoa (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Polymer composites are among the most widely used materials in industrial and engineering applications due to their versatile properties and the potential to enhance their performance through the incorporation of nanomaterials. In this study, the thermal properties of a polyester composite reinforced with halloysite nanoparticles—a type of natural nanotube known for its significant impact on improving the thermal and mechanical performance of polymers—were investigated. This research may open new horizons for the use of such materials in engineering applications. Thermogravimetric analysis (TGA) is one of the most fundamental tests for studying the thermal properties of composites, as it allows for the determination of the material’s thermal degradation behavior and service life in both pure polyesters and polymer/nanoclay (halloysite nanotubes, NHTs) systems. TGA was conducted on polyester/NHTs nanocomposite samples with varying filler concentrations (0 wt%, 0.2, 0.4, 0.8, 1, 2, 4, 6, and 8 wt%). The specimens were prepared with dimensions of 65 mm (length) × 13 mm (width) × 5 mm (thickness) in accordance with ASTM D790M. The thermal property assessments, particularly the thermogravimetric analysis, revealed that the samples containing nanofillers exhibited superior heat resistance, with an optimal enhancement observed at 6–8% nanofiller loading, compared to unfilled polyester and halloysite/polyester matrix composites.